Growing against the background of colonization? Chinese labor market and FDI in a historical perspective - Hao Wang; Jan Fidrmuc; Yunhua Tian (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This article investigates how the legacy of colonization shapes the impact of inward FDI on employment in the Chinese labor market. The analysis utilizes provincial panel on overall employment and employment in the service sector during 2006-15. We find that inward FDI significantly promotes employment and that this relationship is stronger in regions once colonized by Western countries. Conversely, regions with a legacy of Japanese colonization display a weaker, and even negative, relationship between FDI and employment. These findings are robust to controlling for the length and intensity of colonization, as well as for endogeneity of FDI.
URN:NBN:fi:bof-201806011591
Keywords: F21; F54; O15; 330